2015
DOI: 10.1016/j.toxicon.2014.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Anti-loxoscelic horse serum produced against a recombinant dermonecrotic protein of Brazilian Loxosceles intermedia spider neutralize lethal effects of Loxosceles laeta venom from Peru

Abstract: In this work, an anti-loxoscelic serum was produced by immunizing horses with a recombinant dermonecrotic protein from Loxosceles intermedia (rLiD1). Anti-rLiD1 antibodies were able to recognize different species of Loxosceles venoms by Western Blot and ELISA. The efficacy of anti-rLiD1 serum against the toxic effects of Loxosceles laeta (Peru) venom was tested, showing that anti-rLiD1 serum can neutralize those effects. This study confirms that recombinant proteins can be good candidates to replace crude veno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Different studies that investigated the protective effects of recombinant Loxosceles phospholipases-D (PLDs) or even the neutralizing effects of serum produced with these toxins found that the edematogenic activity of Loxosceles venoms is particularly difficult to neutralize and raised the possibility that other venom components may be responsible for edema development [30,31]. LiRecTCTP induces an increase in microvascular permeability of skin vessels and is a component of edema formation with an earlier and faster effect when compared to the inflammatory response triggered by whole L. intermedia venom in mouse paws [2].…”
Section: Discussionmentioning
confidence: 99%
“…Different studies that investigated the protective effects of recombinant Loxosceles phospholipases-D (PLDs) or even the neutralizing effects of serum produced with these toxins found that the edematogenic activity of Loxosceles venoms is particularly difficult to neutralize and raised the possibility that other venom components may be responsible for edema development [30,31]. LiRecTCTP induces an increase in microvascular permeability of skin vessels and is a component of edema formation with an earlier and faster effect when compared to the inflammatory response triggered by whole L. intermedia venom in mouse paws [2].…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising since the antivenom was made using recombinant SMase D toxins, which are thought to not show any fibrinogenolytic activity. This assay revealed that, despite significant reductions described in loxoscelism using recombinant SMase D antivenom [28,30,37], those antivenoms are unlikely to provide any neutralization of fibrinogenolytic toxins and their associated systematic effects. Surprisingly, the highest concentration of antivenom in the negative control showed a decrease in clot strength, where clot strength was negatively correlating with the volume of antivenom added to the sample on TEG.…”
Section: Discussionmentioning
confidence: 95%
“…In addition to local symptoms, in nearly half of the cases, loxoscelism can cause severe systematic medical problems, including hematological disturbances and renal injury, which can progress to hemolysis, thrombocytopenia, shock, disseminated intravascular coagulation, acute renal failure, and even death [1,[4][5][6]. These hematological disturbances are most likely induced by metalloproteases, a few of which have been characterized such as Loxolysin A (20)(21)(22)(23)(24)(25)(26)(27)(28) and Loxolysin B (32)(33)(34)(35) found in L. intermedia venom [9]. Recent L. laeta venom gland transcriptomics identified multiple Loxosceles astacin-like metalloproteases (LALPs) within the 20 to 25 kDa range [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been widely reported that many Loxosceles spp. venom proteins induce the production of non-neutralizing antibodies, later present in the total IgG pool of anti-venoms [32,33]. This brings upon the need for the employment of SMases D or their immunorelevant domains as major immunogens in the immunization process, given the significance of these toxins in the course of envenomation [32,[34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%